Science and science in Muslim theology: exploratory study from the books of Tafsir - Solihin, Sohirin Mohammad (International Islamic University Chittagong (IIUC), 2011)
The paper attempts to reveal the relation between science and religion from Islamic perspective by referring to the views of contemporary Qur'anic exegesis. In addition, it also highlights the sources of sciences based on the divine concept. Moreover, it discusses the status and task of Muslim scientists in developing the civilization. The Qur'ān supports the use of intellectualism to come out with the concept of sciences on the basis of divine guidance. There are many directions in the message related to sciences of biology, preservation of ecology, and medicine.